Impact of donor transaminases on liver transplant utilisation and unnecessary organ discard: national registry cohort study - Dobbins, Joseph J.; Tingle, Samuel J.; Mehew, Jennifer; Thompson, Emily R.; Kourounis, Georgios; McPherson, Stuart; White, Steve A.; Wilson, Colin H. (Frontiers in Transplantation, 2024)
BackgroundDonor liver transaminases (ALT and AST) have been used to decline livers for transplant, despite evidence that they do not influence transplant outcomes. This study assesses the effect that raised donor transaminases have on the unnecessary decline of livers.MethodsThis retrospective cohort study used the National Health Service registry on adult liver transplantation (2016–2019). Logistic regression models were built to assess the impact of donor transaminases on the utilisation of organs donated following brain stem death (DBD) and circulatory death (DCD). A further model was used to simulate the impact on liver decline if raised donor ALT was not used to make utilisation decisions.Results5,424 adult livers were offered for transplant, of which 3,605 were utilised (2,841 DBD, 764 DCD). In multivariable analysis, adjusted for key factors, increasing peak donor ALT independently increased the odds of liver decline (DBD aOR = 1.396, 1.305–1.494, p < 0.001, DCD aOR = 1.162, 1.084–1.246, p < 0.001). AST was also a significant predictor of liver decline. 18.5% of livers from DBD donors with ALT > 40 U/L (n = 1,683) were declined for transplantation. In this group, our model predicted a 48% (38%–58%) decrease in decline if raised donor ALT was excluded from these decisions. This represents an additional 37 (30–45) liver transplants every year in the UK.ConclusionsRaised donor ALT increased the likelihood of liver decline. As it does not influence transplant outcome, avoiding donor ALT-based organ decline is an immediate and effective way to expand the donor pool.